Issues of reforming professional medical education in Russia - S. Yu. Astanina (Кардиоваскулярная терапия и профилактика, 2022)
The reform of higher education is directly related to the solution of problems arising in the medical education system. The article describes the activities of the Section for the development of educational activities of therapeutic departments within the framework of the Russian Society for the Prevention of Noncommunicable Diseases, created to unite qualified teachers of medical education in solving problems of improving the efficiency of the process of training medical personnel in the specialty “Therapy”. The article discusses the organization of the project of the Russian Society for the Prevention of Noncommunicable Diseases on additional issues of the scientific and practical journal “Cardiovascular Therapy and Prevention. Professional education”, as well as the activities of the Section.